Evaluation of Mechanical and Thermal Performance of Polyethylene Terephthalate Recycled Ribbon and Carbon‐Reinforced Compatibilized Polypropylene. Issue 3 (17th December 2019) - Saifullah, Abul B.M.; Inampudi, Venkata V.K.; Nikzad, Mostafa; Sbarski, Igor; Hussain, Manwar
Abstract : Polypropylene (PP) and polyethylene terephthalate (PET) are the two most widely used plastics, which are not compatible with recycling as a blend. In this research work, two different compositions of recycled PP/PET ribbon 65/35 (v/v %) and 78/22 (v/v%) along with 5% (wt%) of polypropylene‐grafted maleic anhydride (PP‐ g ‐MAH) as compatibilizer were blended, 2– 5 wt% of carbon fiber ( CF ) was further added for reinforcement. The compositions of these materials are mechanically mixed and extruded by a twin‐screw extruder to make pellets. These pellets are then used to produce standard samples by injection molding for evaluation. The molded samples were tested under tensile, flexural and impact loads to evaluate mechanical properties. Scanning electron microscopy (SEM) was conducted on the fracture surface of the impact‐tested samples to understand polymer blend morphology. Differential scanning calorimetry (DSC) and dynamic mechanical analysis (DMA) also carried out to check the thermal properties, mainly transition temperatures ( T g ) and heat flow. These test results compared, which show substantial improvement in mechanical properties by adding CF and compatibilizer, without much change in transition temperatures. POLYM. ENG. SCI., 60:575–580, 2020. © 2019 Society of Plastics Engineers